Penilaian Kualitas Informasi Dokumen Rekam Medis Pasien Rawat Inap Pada Kasus Cerebral Infarction di RSUD Sleman D.I.Yogyakarta - Dianatus Solehah; Feby Erawantini; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
The assessment of the quality of medical record document information can help to find out the scores thatdetermine the level of quality of information produced by inpatient medical record documents in cases ofcerebral infarction. Based on preliminary studies, it has been carried out at Sleman District GeneralHospital. Yogyakarta on February 26, 2020 found a problem related to the contents of incomplete medicalrecord documents. This study aims to assess the quality of inpatient medical record document informationin the case of Cerebral Infarction in Sleman D.I.Yogyakarta Hospital. Descriptive method and crosssectional research design by observing 23 medical record documents taken from the sampling resultsusing the Slovin method to obtain a sample of 204 populations related to cases of cerebral infarction in theinpatient unit. Research results The assessment of the quality of information on medical record documentsuses four dimensions of product and service performance for information quality. Dimension assessmentwas considered good because of the results of 13 scores in filling out the inpatient medical recorddocuments that became the study sample. The contents of medical record documents which wereconsidered to be still poor were the contents of the clarity of the doctor's writing and the completeness ofthe name and signature of the care provider, one of which was at the DPJP.